2008
DOI: 10.1183/09031936.00104007
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide/formoterol maintenance and reliever therapy: impact on airway inflammation in asthma

Abstract: The aim of the present study was to compare the effectiveness, safety and health economics of budesonide/formoterol maintenance and a novel reliever therapy with conventional best practice in patients with persistent asthma in Canada.After 2 weeks of usual therapy, 1,538 patients were randomised for 6 months to open-label budesonide/formoterol maintenance and reliever therapy 160/4.5 mg twice daily and as needed, or to guideline-based conventional best practice. Severe asthma exacerbations, reliever medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
2
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 17 publications
7
74
2
7
Order By: Relevance
“…The lung weight values reflect lung inflammatory oedema while the values for ELGV reflect the severity of bronchoconstriction, mucus plugging, and also to a certain extent, oedema [8]. We have also observed that the inflammatory as compared to 5% decrease (p=0.97) by conventional best practice therapy (based on maintenance dosing) [12].…”
Section: Discussionsupporting
confidence: 51%
“…The lung weight values reflect lung inflammatory oedema while the values for ELGV reflect the severity of bronchoconstriction, mucus plugging, and also to a certain extent, oedema [8]. We have also observed that the inflammatory as compared to 5% decrease (p=0.97) by conventional best practice therapy (based on maintenance dosing) [12].…”
Section: Discussionsupporting
confidence: 51%
“…For these Figure 6. Change in sputum eosinophil count in patients receiving budesonide/formoterol as maintenance and reliever therapy or conventional best practice (71). Patients in the budesonide/ formoterol maintenance and reliever therapy group received 748 lg/day ICS in BDP equivalents and patients in the conventional best practice (CBP) treatment group received 1015 lg/day ICS in BDP equivalents (P < 0.0001).…”
Section: Practical Considerations For Physicians Using Budesonide/ Fomentioning
confidence: 99%
“…Sears et al conducted a study in a subgroup of patients to examine the changes in induced sputum eosinophil count in patients receiving budesonide/formoterol maintenance and reliever therapy (160/4.5 lg b.i.d.) compared with conventional best practice and concluded that budesonide/formoterol maintenance and reliever therapy achieved similar control of eosinophilic inflammation compared with conventional best practice, despite a lower mean ICS dose (71) (Fig. 6).…”
Section: Safety Of Budesonide/formoterol Maintenance and Reliever Thementioning
confidence: 99%
See 1 more Smart Citation
“…Diese und andere synergistische Wirkungen von Budesonid und Formoterol tragen mit Wahrscheinlichkeit zu den beobachteten positiven Effekten der festen Budesonid-Formoterol-Kombination in der Erhaltungs-und Bedarfstherapie bei (Übersichten bei [12,39]). Eine kanadische Untersuchung belegt darüber hinaus, dass eine SMART-Therapie trotz des geringeren Bedarfs an Glukokortikoiden selbst einer optimalen konventionellen Asthmatherapie im Hinblick auf Parameter der asthmatischen Schleimhautentzündung zumindest gleichwertig ist [40].…”
unclassified